Evaluating PET‐CT in the detection and management of recurrent cervical cancer: systematic reviews of diagnostic accuracy and subjective elicitation. (3rd December 2013) - Meads, C; Davenport, C; Małysiak, S; Kowalska, M; Zapalska, A; Guest, P; Martin‐Hirsch, P; Borowiack, E; Auguste, P; Barton, P; Roberts, T; Khan, K; et al.
<x xml:space="preserve">Abstract</x> Background Positron emission tomography–computed tomography (PET‐CT) is recommended to triage women for exenterative surgery and surveillance after treatment for advanced cervical cancer. Objective To evaluate diagnostic accuracy of additional whole body PET‐CT compared with CT/magnetic resonance imaging (MRI) alone in women with suspected recurrent/persistent cervical cancer and in asymptomatic women as surveillance. Design Systematic reviews. Subjective elicitation to supplement diagnostic information. Search strategy/Selection criteria/Data collection and analysis Searches of electronic databases were performed to June 2013. Studies in women with suspected recurrent/persistent cervical cancer and in asymptomatic women undergoing follow up with sufficient numeric data were included. We calculated sensitivity, specificity and corresponding 95% confidence intervals. Meta‐analyses employed a bivariate model that included a random‐effects term for between‐study variations (CT studies) and univariate random effects meta‐analyses (PET‐CT studies) for sensitivity and specificity separately. Subjective elicitation Prevalence of recurrence and the accuracy of imaging elicited using the allocation of points technique. Coherence of elicited subjective probabilities with estimates in the literature examined. Results We identified 15 relevant studies; none directly compared additional PET‐CT with MRI or CT separately. Most CT and MRI studies used older protocols and the majority did not distinguish between asymptomatic and symptomatic women. Meta‐analysis of nine PET‐CT studies in mostly symptomatic women showed sensitivity of 94.8 (95% CI 91.2–96.9), and specificity of 86.9% (95% CI 82.2–90.5). The summary estimate of the sensitivity of CT for detection of recurrence was 89.64% (95% CI 81.59–94.41) and specificity was 76% (95% CI 43.68–92.82). Meta‐analysis for MRI test accuracy studies was not possible because of clinical heterogeneity. The sensitivity and specificity of MRI in pelvic recurrence varied between 82 and 100% and between 78 and 100%, respectively. Formal statistical comparisons of the accuracy of index tests were not possible. Subjective elicitation provided estimates comparable to the literature. Subjective estimates of the increase in accuracy from the addition of PET‐CT were less than elicited increases required to justify the use in PET‐CT for surveillance. Conclusion Evidence to support additional PET‐CT is scarce, of average quality and does not distinguish between application for surveillance and diagnosis. Guidelines recommending PET‐CT in recurrent cervical cancer need to be reconsidered in the light of the existing evidence base.